High-sucrose effect on bone structure, hardness and biomechanics in an obesity model using Wistar male rats - Carvalho, Antonio Augusto Ferreira [UNESP]; Nakamune, Ana Cláudia de Melo Stevanato [UNESP]; Biffe, B. G. [UNESP]; Louzada, Mário Jefferson Quirino [UNESP] (My University, 2012)
Introduction: Excessive consumption of sugar-sweetened beverage is positively related to overweight. Despite the epidemic of childhood obesity, body mass can have a positive or negative effect on bone health. Material and methods: Wistar rats 8 weeks olds were randomly assigned to consume water (Control group, n = 10), sucrose 30% (HS group, n = 10) and water + sucrose 30% (WHS group, n = 14) for 8 weeks. All animals received standard laboratory chow ad libitum. Femur measurements included microhardness, bone mineral density (BMD) by DXA, mechanical compression test and microcomputed tomography (microCT) analysis. Results: We observed significant difference in final body weight in HS and WHS groups, significant increase in triacylglycerol/fructosamine in HS and WHS groups, significantly high BMD in WHS group, increased periosteal/endosteal cortical microhardness in WHS group. Compared with control, microCT parameters evidenced lower amount of connected trabecular bone, decreased bone volume, lower trabecular number with high trabecular separation in distal epiphysis in WHS animals. Conclusion: High-sucrose consumption causes obesity induced by a liquid diet with negative effects on cancellous bone.
Keywords: Cortical bone; Obesity; Rats; Sucrose; Trabecular boné